The Relationship Between Promotion and Students' Interest in Participating in Barista Training at the Job Training Center (BLK) - Khairani Annisa; Alim Harun Pamungkas (Universitas Negeri Padang, 2021)
This research is motivated by the high interest of students in participating in barista training at BLK Padang, this is presumably because the promotion carried out by BLK Padang is very good. This study aims to describe the promotion of BLK Padang, describe the interest of students in participating in barista training, and see the relationship between promotions and the interest of students in participating in Barista Training at the Job Training Center (BLK) Padang. This type of research is quantitative research with correlational descriptive technique. The study population was all participants of the third and fourth batch of 2020 Barista training at BLK Padang and samples were taken using a sampling technique, namely simple random sampling. The data collection technique used in this study used google form in distributing online questionnaires. The data analysis technique used the percentage formula and spearmen rho. The results showed that: the promotion of the Job Training Center (BLK) Padang was categorized as very good, the students' interest in participating in the barista training was categorized as very high, and there was a significant relationship between the promotion and the students' interest in participating in the barista training at the Job Training Center (BLK) Padang. Furthermore, it is recommended for managers to explore more effective and efficient ways of promotion so that other trainings also have a high interest such as barista training and for other researchers to be able to choose other variables that are also related to interest in participating in training.